Teenagers and chat (Journal of Parents and Teachers, 2014)
Chatting is one of the favorite activities of adolescents and one to which they spend more time. In this article, several questions are asked to know better what adolescents do in chats.
Keywords: chat; adolescence; social networks; communication.